IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PELAKSANAAN PELAYANAN PUBLIK PENGURUSAN AKTA JUAL BELI TANAH DI KECAMATAN TEGALSARI KABUPATEN BANYUWANGI - Zaki Al Mubarok (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
This research aims to know us For the implementation of the principles of good governance that is run by a Head as a PPAT in the service of making the deed of sale and purchase of land (AJBT) in Subdistrict Office of Tegalsari and to know the factors that encourage the invited, the principles of good governance in the public service. This research uses descriptive qualitative approach in accordance with the concept of Miles and Hubberman. Data that has been collected in this study will be analyzed using descriptive analysis with model analysis of data by Miles and Huberman. The results of this research is in the application of the principles of good governance in the public service, especially the principle of participation, provision and the applicable rules, the principle of transparency, and the principle of responsive camat has provided the best, although there are some citizens according to the results of the interview said the head as a PPAT tend favoritism against residents who are financially capable and less-capable citizens. In general the public service which set out the principles of good governance that is in the Sub-District of Tegalsari Banyuwangi Regency has been executed well, though not completely. The factors that encourage the invited, the principles of good governance in the public service is the principle of participation, provision and the applicable rules, the principle of transparency, and responsiveness.